2002
DOI: 10.1300/j010v35n01_08
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific and Culture-Specific Coping Strategies Used by Mainland Chinese Immigrants During Resettlement in Hong Kong

Abstract: A qualitative study was undertaken to explore the stage-specific and culture-specific coping strategies used by Mainland Chinese immigrants in Hong Kong to handle psychosocial stressors experienced during the resettlement stage of the migration process. While direct action coping strategies of problem-solving and compromise were used by immigrants to deal with recurring, daily resettlement difficulties, cognitive strategies of positive comparisons and positive and optimistic thinking were utilized to change th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
6
35
0
Order By: Relevance
“…One explanation is that poor coping strategies, such as avoidance, have been demonstrated to exacerbate the impact of childhood trauma on later substance abuse [28], [29]. In general, Chinese tend to use acceptance and avoidance as ways to cope with difficult situations [30]. One survey among 512 Chinese heroin users found that over seventy percent of these patients have avoidant personality traits [31].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that poor coping strategies, such as avoidance, have been demonstrated to exacerbate the impact of childhood trauma on later substance abuse [28], [29]. In general, Chinese tend to use acceptance and avoidance as ways to cope with difficult situations [30]. One survey among 512 Chinese heroin users found that over seventy percent of these patients have avoidant personality traits [31].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on Chinese international students in Australia, two coping strategies were identified: problem-solving and seeking social support (Le & Liu, 2007). In another study on Chinese immigrants' resettlement in Hong Kong, problemsolving and seeking social support were reported to be the most widely used coping strategies (Wong, 2002). To assist Chinese international students to use these strategies effectively, practitioners first must be aware of the common sources of the problems that the students may have (as was previously discussed in this article).…”
Section: Health Providers and Mental Health Social Workersmentioning
confidence: 94%
“…Statistics have shown that about half of these immigrants are adults. Of these, more than 80% are women in their thirties and forties, many of whom immigrate with school-age children (Wong, 2002). Though Hong Kong and Mainland China share the same written language, the majority of Hong Kong Chinese speak Cantonese.…”
Section: Study 1: Mainland Chinese Immigrants In Hong Kongmentioning
confidence: 99%